Generalized model of holographic recording in photopolymer materials - Karpov, H.M.; Obukhovsky, V.V.; Smirnova, T.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
The generalized diffusion model of holographic recording in photopolymer materials has been offered. The theoretical description of hologram formation process is based on the concept of free volume redistribution and using the generalized diffusion equation. Free volume is produced in photopolymer medium due to the polymer shrinkage effect. The developed theory allows to take into account influence of inhomogeneous monomer distribution during recording process and shrinkage rate on a kinetics of a hologram formation. The principal influence of the diffusion/polymerization rates ratio on the hologram properties has been shown. The offered model allows also to describe relief formation process on the surface of a recording layer.